Effect of camel milk and pistachio-based product on cancer-induced sarcopenia in Sprague Dawley rats - Zahid, Asna; Zahoor, Tahir; Sameen, Aysha; Faisal, Muhammad Naeem (Food Science and Technology, 2023)
In the current study, we investigated the role of camel milk and pistachio in the muscle growth of rats with cancer-induced sarcopenia. Female Sprague Dawley rats weighing 180 – 200 grams were selected for a bioefficacy trial for 13 weeks and divided into four groups: G1 (negative control), G2 (positive control), G3 (normal diet + camel milk), and G4 (normal diet + camel milk and pistachio based product). Tumors were induced in rats by administering 50 mg/kg of 7,12-dimethylbenz(a)anthracene via gastrogavage followed by chemotherapy in G2, G3, and G4. Histopathological analysis, muscle strength analysis, muscle fiber histology and renal function tests were performed. The administration of camel milk and pistachio-based product (CMP) significantly (P<0.01) improved muscle strength in the treatment group. Muscle mass analysis of the extensor digitorum longus (EDL) and soleus muscle showed significant (P<0.01) improvement in the treatment group. Muscle fiber diameter also significantly (P<0.01) increased in the treatment group. Camel milk and pistachio-based product (CMP) have shown promising effects against cancer-induced sarcopenia in rat modelling by enhancing muscle function and strength.